2023
DOI: 10.1038/s43247-023-00697-6
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater deeper than 500 m contributes less than 0.1% of global river discharge

Abstract: Groundwater is one of the largest reservoirs of water on Earth but has relatively small fluxes compared to its volume. This behavior is exaggerated at depths below 500 m, where the majority of groundwater exists and where residence times of millions to even a billion years have been documented. However, the extent of interactions between deep groundwater (>500 m) and the rest of the terrestrial water cycle at a global scale are unclear because of challenges in detecting their contributions to streamflow. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Over the past two decades, there has been an increase in the awareness of the microbial communities that inhabit the deep subsurface of depths of up to a few km (Bar-On et al, 2018;Magnabosco et al, 2018;McMahon & Parnell, 2014). This has been accompanied by questions about how the deep subsurface fits within the larger Earth system in terms of microbial life and associated water and geochemical fluxes (Ferguson et al, 2021(Ferguson et al, , 2023Lollar et al, 2019;Warr et al, 2018). As we stand at the precipice of the energy transition, we have the opportunity to develop the deep subsurface in a manner that allows us to study its natural functions and response to anthropogenic perturbations to minimize human impacts and build understanding, synergies and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past two decades, there has been an increase in the awareness of the microbial communities that inhabit the deep subsurface of depths of up to a few km (Bar-On et al, 2018;Magnabosco et al, 2018;McMahon & Parnell, 2014). This has been accompanied by questions about how the deep subsurface fits within the larger Earth system in terms of microbial life and associated water and geochemical fluxes (Ferguson et al, 2021(Ferguson et al, , 2023Lollar et al, 2019;Warr et al, 2018). As we stand at the precipice of the energy transition, we have the opportunity to develop the deep subsurface in a manner that allows us to study its natural functions and response to anthropogenic perturbations to minimize human impacts and build understanding, synergies and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…CCS is arguably the most important of these projected uses in terms of reducing greenhouse gas emissions, with many of the studies examining the capacity to sequester carbon in the subsurface focusing on estimation of the volume of porosity in sedimentary basins suited for this purpose (Benson & Cole, 2008;Krevor et al, 2023;Zoback & Smit, 2023). Additional (Ferguson et al, 2023). Current geothermal projects are associated with smaller fluxes (C. E. Clark et al, 2010;IEA, 2021a).…”
Section: The Future Of the Subsurfacementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the magnitude of such upflow of deep groundwater is deemed to be minor relative to total streamflow. Ferguson et al (2023) used a chloride mass balance approach to quantify the global contribution of deep groundwater (depth > 500 m) to global streamflow. They estimated that deep groundwater likely contributed <0.1% to global streamflow and concluded that deep groundwater was only weakly and sporadically connected to the rest of the water cycle on geological timescales, thereby supporting our compartmentalization of the terrestrial water cycle.…”
mentioning
confidence: 99%